Robust Part Quality by Controlling the Injection Moulding Process with 24 Fraction Factorial Design: A Case Study - Sokkalingam, Rajalingam (Institute of Electrical and Electronics Engineers, Inc., 2010)
The author wants to use a case study to investigate the injection moulding machine parameters which will affect the horizontal length dimension of a plastic component used in digital camera. Currently the injection moulding machine process setting caused variations in the diameter exceeding the specification limit. Therefore the experiment is needed to identify the process factors that could be set to maintain the horizontal length dimension closest to the target value and smallest possible variation. The experimental model is used to investigate four factors to identify the factors having large effect by using the Full Factorial Design of Experiment (DOE). The experiment has emphasized the use of these designs in identifying the subset of factors that are active and provide some information about the interaction.